ANALISIS MINAT MENGGUNAKAN BRI MOBILE (Survei Pada Nasabah Bank Rakyat Indonesia (Persero) Tbk. Kota Sukabumi) - Hermawann, Larasati Dewi; Komariah, Kokom; Danial, R. Deni Muhammad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The research aims to measure how much influence the perception of ease of use, perceived usefulness and perceived security of interest in using. The variables used in this study are perceived ease of use (X1), perceived usefulness (X2), perceived security (X3) and interest in using (Y). The method used in this study uses a purposive sampling method by distributing questionnaires to 200 respondents of Bank Rakyat Indonesia customers in Sukabumi City. The analysis technique used is multiple linear regression measuring the effect partially and simultaneously. The results obtained indicate a positive and significant effect between perceived ease of use, perceived usefulness and perceived security of interest in using.